Behaviour of tubular joints subjected to combined loadings - Yeoh, Seng Keat. (2009)
Fatigue analysis of offshore structures requires accurate information on the peak hot spot stress (peak HSS) of tubular joints. To date, literature on the location and magnitude of the peak HSSs of tubular joints subjected to combined loadings is still not widely available. In this project, experimental testing of a tubular T-joint and a tubular K joint full scale steel specimen, subjected to various basic and combined loadcases was conducted. In addition, numerical analyses of T and K joints using finite element models was carried out. The experimental SCFs of the basic loadcases for the T-joint specimen were found to be in good agreement with the author's FE results and other authors' predicted SCFs.